2017
DOI: 10.1515/ap-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Oochoristica (Cyclophyllidea: Linstowiidae) from non-native Mediterranean geckos, Hemidactylus turcicus (Sauria: Gekkonidae), from Texas, USA

Abstract: A new species of cyclophyllidean tapeworm, Oochoristica harschi sp. nov. is described from 2 of 18 (11%) non-native Mediterranean geckos (Hemidactylus turcicus) collected in June 2016 from Tom Green County, Texas, USA The new species has few characteristics in common with 17 species of Oochoristica previously described from Nearctic reptiles. Of this group, O. harschi is most similar to O. macallisteri Bursey and Goldberg, 1996 from the side-blotched lizard, Uta stansburiana from Arizona and California, USA, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Oochoristica mutabili is considered a heteroxenous cestode that requires a suitable intermediate host [39] . The species of Oochoristica are cosmopolitan infecting more than 56 species of reptilian hosts, occasionally in mammals, and rare in amphibians [40][41][42][43] . Genus Oochoristica includes about 88 species, only O. mutabili, O. truncata, and O. fibrata were previously recorded in Egypt [9,41,44] .…”
Section: Discussionmentioning
confidence: 99%
“…Oochoristica mutabili is considered a heteroxenous cestode that requires a suitable intermediate host [39] . The species of Oochoristica are cosmopolitan infecting more than 56 species of reptilian hosts, occasionally in mammals, and rare in amphibians [40][41][42][43] . Genus Oochoristica includes about 88 species, only O. mutabili, O. truncata, and O. fibrata were previously recorded in Egypt [9,41,44] .…”
Section: Discussionmentioning
confidence: 99%
“…Snout-vent length (SVL in mm) of lizard specimens were recorded after several years of storage in 70% ethanol. Helminth identification was facilitated by utilizing descriptions and illustrations in Anderson et al (2009) for genera, and Bursey Goldberg (2015), Lhermitte et al (2008), and Morgan (1945) for species; cestode identification was confirmed following Rausch (1994), McAllister Bursey (2017), andMcAllister et al (2013); Estrada-PeÑa et al (2014 were consulted for tick identification. Identification guides generally illustrate only male Sk rjabinelazia and we found only females in our samples; those females, however, most closely resembled illustrations of S. taurica.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises cestodes parasitizing reptiles and is cosmopolitan in its distribution. Within this group, which includes about 88 species (Bursey et al, 2010) and more species have been added recently (Mašová et al, 2010; Schuster, 2011; Bursey & Goldberg, 2011; Mašová et al, 2012; McAllister & Bursey, 2017) about 17 species are known from Palearctic. Oochoristica tuberculata (Rudolphi, 1819) was chosen as type species.…”
Section: Discussionmentioning
confidence: 99%